2015
DOI: 10.1038/ncomms8049
|View full text |Cite
|
Sign up to set email alerts
|

dDsk2 regulates H2Bub1 and RNA polymerase II pausing at dHP1c complex target genes

Abstract: dDsk2 is a conserved extraproteasomal ubiquitin receptor that targets ubiquitylated proteins for degradation. Here we report that dDsk2 plays a nonproteolytic function in transcription regulation. dDsk2 interacts with the dHP1c complex, localizes at promoters of developmental genes and is required for transcription. Through the ubiquitin-binding domain, dDsk2 interacts with H2Bub1, a modification that occurs at dHP1c complex-binding sites. H2Bub1 is not required for binding of the complex; however, dDsk2 deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 70 publications
4
46
0
Order By: Relevance
“…In yeast, cycles of H2B ubiquitination and deubiquitination are needed for a productive switch from transcription initiation to elongation (Henry et al, 2003). Recent studies indicate a direct link between H2B deubiquitination at promoter regions and decreased transcription in Drosophila and mammalian cells (Kessler et al, 2015; Sussman et al, 2013). In addition, in vitro analyses using chemically defined nucleosome arrays containing recombinant H2Bub1 (Fierz et al, 2011) demonstrated that H2Bub1 can disrupt higher-order chromatin architectures, facilitating more open, accessible conformations needed for transcription.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, cycles of H2B ubiquitination and deubiquitination are needed for a productive switch from transcription initiation to elongation (Henry et al, 2003). Recent studies indicate a direct link between H2B deubiquitination at promoter regions and decreased transcription in Drosophila and mammalian cells (Kessler et al, 2015; Sussman et al, 2013). In addition, in vitro analyses using chemically defined nucleosome arrays containing recombinant H2Bub1 (Fierz et al, 2011) demonstrated that H2Bub1 can disrupt higher-order chromatin architectures, facilitating more open, accessible conformations needed for transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Second, HP1b overexpression decompacts pericentromeric heterochromatin and decreases binding to HP1a and H3K9me2 to it, suggesting that the presence of HP1b counteracts the function of HP1a in heterochromatin (Zhang et al, 2011). Third, euchromatic HP1c functions in a complex with two related Zn-fingercontaining transcription factors, Without Children (WOC) and Relative of WOC (ROW) (Font-Burgada et al, 2008) and ubiquitin receptor protein Dsk2 (also known as Ubiquilin) (Kessler et al, 2015), as a positive regulator of transcription. A recent comprehensive bioinformatic analysis has revealed that significant common targeting genes and unique genes are altered in HP1knockdown S2 cells of Drosophila (Lee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2010). Furthermore, HP1C has been implicated previously in release from promoter proximal pausing (K essler et al . 2015), and HP1a and HP1C have been associated with pausing at transcribed genes (S akoparnig et al .…”
Section: Resultsmentioning
confidence: 98%
“…2005), and HP1C is known to be targeted to chromatin by the DNA binding Zinc Finger transcription factors WOC and ROW (F ont -B urgada et al . 2008; K essler et al . 2015; D i M auro et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation